The development of a staphylococcus aureus four antigen vaccine for use prior to elective orthopedic surgery. Issue 2 (1st February 2019) - Gurtman, A.; Begier, E.; Mohamed, N.; Baber, J.; Sabharwal, C.; Haupt, R.M.; Edwards, H.; Cooper, D.; Jansen, K.U.; Anderson, A.S.
ABSTRACT: Staphylococcus aureus ( S. aureus ) is a challenging bacterial pathogen which can cause a range of diseases, from mild skin infections, to more serious and invasive disease including deep or organ space surgical site infections, life-threatening bacteremia, and sepsis. S. aureus rapidly develops resistance to antibiotic treatments. Despite current infection control measures, the burden of disease remains high. The most advanced vaccine in clinical development is a 4 antigen S. aureus vaccine (SA4Ag) candidate that is being evaluated in a phase 2b/3 efficacy study in patients undergoing elective spinal fusion surgery ( STaphylococcus aureus suRgical Inpatient Vaccine Efficacy [STRIVE]). SA4Ag has been shown in early phase clinical trials to be generally safe and well tolerated, and to induce high levels of bactericidal antibodies in healthy adults. In this review we discuss the design of SA4Ag, as well as the proposed clinical development plan supporting licensure of SA4Ag for the prevention of invasive disease caused by S. aureus in elective orthopedic surgical populations. We also explore the rationale for the generalizability of the results of the STRIVE efficacy study (patients undergoing elective open posterior multilevel instrumented spinal fusion surgery) to a broad elective orthopedic surgery population due to the common pathophysiology of invasive S. aureus disease and commonalties of patient and procedural risk factors for developing postoperative S. aureus surgical site infections.